Descriptive Analysis of Venous Thromboembolism in Georgia Trauma Centers Compared with National Trauma Centers Participating in the Trauma Quality Improvement Program. Issue 11 (November 2017) - Lassiter, Randi L.; Ashley, Dennis W.; Medeiros, Regina S.; Adam, Bao-ling; Nesmith, Elizabeth G.; Johns, Tracy J.; Atkins, Elizabeth V.; Dente, Christopher J.; Ferdinand, Colville H.
This study was designed to compare the incidence of venous thromboembolism (VTE) in Georgia trauma centers with other national trauma centers participating in the Trauma Quality Improvement Program (TQIP). The use of chemoprophylaxis and characteristics of patients who developed VTE were also examined. We conducted a retrospective observational study of 325, 703 trauma admissions to 245 trauma centers from 2013 to 2014. Patient demographics, rate of VTE, as well as the use, type, and timing of chemoprophylaxis were compared between patients admitted to Georgia and non-Georgia trauma centers. The rate of VTE in Georgia trauma centers was 1.9 per cent compared with 2.1 per cent in other national trauma centers. Overall, 49.6 per cent of Georgia patients and 45.5 per cent of patients in other trauma centers had documented chemoprophylaxis. Low molecular weight heparin was the most commonly used medication. Most patients who developed VTE did so despite receiving prophylaxis. The rate of VTE despite prophylaxis was 3.2 per cent in Georgia and 3.1 per cent in non-Georgia trauma centers. Mortality associated with VTE was higher in Georgia trauma centers compared with national TQIP benchmarks. The incidence of VTE and use of chemoprophylaxis within Georgia trauma centers were similar to national TQIP data. Interestingly, most patients who developed VTE in both populations received VTE prophylaxis. Further research is needed to develop best-practice guidelines for prevention, early detection, and treatment in high-risk populations.